Pengembangan Kompetensi Profesional Guru dalam Menghadapi Sertifikasi - Ade Cahyana (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
Certification of teacher have been accounted for as one of the education core reforms to improve teacher professionalism. The release of the Act No. 14/ 2006 for Teacher and Lecturer (atÂ higher education) is noticeable to be a historical tombstone which sets teacher and lecturer as profession as well as doctor, engineer or others. This will change the public perception to teacher to become more positive, to build up the teacher self-confident, and to magnetize the interest of those first quality candidates to turn out to be teachers, and to give the public trust back to school as an educational institution. It isÂ highly recommended that the enhancement of teacher professional capacity to be integrated with the instructional activities implemented at schools, which, on one hand are capable of improving their quality of teaching as teachers, on the other hand capable of giving them the opportunities to improve their professional capacity while toting-up their cummulative credits mandatory for teacher certification.Â ABSTRAKSertifikasi guru dinilai sebagai salah satu kebijakan reformasi pendidikan untuk meningkatkan profesionalisme guru. Keluarnya Undang-Undang Nomor 14/2006 tentang Guru dan Dosen adalah merupakan tonggak sejarah tentang bagaimana guru dan dosen diakui sejajar sebagai pekerja profesi sebagaimana pula dokter, insinyur, atau profesi lainnya. Hal ini akan mengubah opini publik terhadap guru menjadi semakin positif, selain juga akan meningkatkan kepercayaan diri mereka, juga akan menarik minat orang-orang yang potensial dan berkualitas untuk menjadi guru, serta mengembalikan kepercayaan masyarakat kepada sekolah sebagai lembaga pendidikan yang berwibawa. Berdasarkan elaborasi aspek aspek profesi guru, sangat disarankan bahwa peningkatan kemampuan profesional guru merupakan kegiatan yang terintegrasi dengan kegiatan pembelajaran di sekolah, satu sisi mampu meningkatkan kualitas mengajar mereka sebagai guru, di sisi lain dapat memberi peluang bagi mereka meningkatkan kemampuan profesional sekaligus menambah kredit akumulatif mereka untuk kepentingan sertifikasi.